Chemistry and Biology studies on anti-inflammiatory bile acid derivatives - LIU, SU (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2019)
Abstract The objective of the dissertation is to clarify the potency, cytotoxicity and metabolism of novel steroidal anti-inflammatory compounds in the treatment inflammatory bowel disease (IBD). Biochemical methods with the purpose of understanding the relationship among chemical structure, potency and adverse effects. In the first chapter, there is a discussion in relation to bile acids (BAs) structure, function, metabolism and their effect on maintaining health in general circumstances and their role in causing enterohepatic disease under pathological conditions. In chapter two, there is a discussion on the physiology and diseases of colon and the potential role of bile acids in colorectal disease. This chapter also presents some studies into the effect of some endogenous BAs on cell death and on cytoprotection in the intestinal epithelial cell line Caco-2. The third Chapter reviews the medicinal chemistry and biological activities of ursodeoxycholic acid (UDCA). This Chapter describes the design and synthesis of novel UDCA derivatives including an amide, a triazole and a sulfonamide. The anti-inflammatory effect of these derivatives and their ability to activate the glucocorticoid receptor (GR) were examined in order to find a structural prototype with better potency/efficacy. The cytotoxicity in liver and colon cells of these compounds was also assessed in order to find a derivative with cell protection ability. Their evaluation in different cells reveals different levels of activity especially on NF-kB activity and the related secretion of proinflammatory cytokines IL-6 and IL-8.
APPROVED
Keywords: IBD; UDCA; inflammation